Question
upstudy study bank question image url

(h) \( (x+1)^{2}=(x-1)(x+5) \) (j) \( 3-\frac{x-2}{5}=2 \) (l) \( \frac{x-2}{2}+\frac{x-1}{3}=2 \frac{5}{6} \) (n) \( \frac{x-1}{4}-\frac{x-2}{8}=\frac{x-4}{2}-1 \)

Ask by Whittaker Logan. in South Africa
Feb 25,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The solutions to the equations are: 1. \( x = 3 \) 2. \( x = 7 \) 3. \( x = 5 \) 4. \( x = 8 \)

Solution

Solve the equation \( (x+1)^{2}=(x-1)(x+5) \). Solve the equation by following steps: - step0: Solve for \(x\): \(\left(x+1\right)^{2}=\left(x-1\right)\left(x+5\right)\) - step1: Multiply the terms: \(\left(x+1\right)^{2}=x^{2}+4x-5\) - step2: Expand the expression: \(x^{2}+2x+1=x^{2}+4x-5\) - step3: Cancel equal terms: \(2x+1=4x-5\) - step4: Move the expression to the left side: \(2x-4x=-5-1\) - step5: Add and subtract: \(-2x=-5-1\) - step6: Add and subtract: \(-2x=-6\) - step7: Change the signs: \(2x=6\) - step8: Divide both sides: \(\frac{2x}{2}=\frac{6}{2}\) - step9: Divide the numbers: \(x=3\) Solve the equation \( 3-\frac{x-2}{5}=2 \). Solve the equation by following steps: - step0: Solve for \(x\): \(3-\frac{x-2}{5}=2\) - step1: Multiply both sides of the equation by LCD: \(\left(3-\frac{x-2}{5}\right)\times 5=2\times 5\) - step2: Simplify the equation: \(17-x=10\) - step3: Move the constant to the right side: \(-x=10-17\) - step4: Subtract the numbers: \(-x=-7\) - step5: Change the signs: \(x=7\) Solve the equation \( \frac{x-2}{2}+\frac{x-1}{3}=2 \frac{5}{6} \). Solve the equation by following steps: - step0: Solve for \(x\): \(\frac{x-2}{2}+\frac{x-1}{3}=2\frac{5}{6}\) - step1: Convert the expressions: \(\frac{x-2}{2}+\frac{x-1}{3}=\frac{17}{6}\) - step2: Multiply both sides of the equation by LCD: \(\left(\frac{x-2}{2}+\frac{x-1}{3}\right)\times 6=\frac{17}{6}\times 6\) - step3: Simplify the equation: \(5x-8=17\) - step4: Move the constant to the right side: \(5x=17+8\) - step5: Add the numbers: \(5x=25\) - step6: Divide both sides: \(\frac{5x}{5}=\frac{25}{5}\) - step7: Divide the numbers: \(x=5\) Solve the equation \( \frac{x-1}{4}-\frac{x-2}{8}=\frac{x-4}{2}-1 \). Solve the equation by following steps: - step0: Solve for \(x\): \(\frac{x-1}{4}-\frac{x-2}{8}=\frac{x-4}{2}-1\) - step1: Multiply both sides of the equation by LCD: \(\left(\frac{x-1}{4}-\frac{x-2}{8}\right)\times 8=\left(\frac{x-4}{2}-1\right)\times 8\) - step2: Simplify the equation: \(x=4x-24\) - step3: Move the variable to the left side: \(x-4x=-24\) - step4: Subtract the terms: \(-3x=-24\) - step5: Change the signs: \(3x=24\) - step6: Divide both sides: \(\frac{3x}{3}=\frac{24}{3}\) - step7: Divide the numbers: \(x=8\) The solutions to the given equations are: 1. \( x = 3 \) 2. \( x = 7 \) 3. \( x = 5 \) 4. \( x = 8 \)

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

The Deep Dive

For the equation \( (x+1)^{2}=(x-1)(x+5) \), you can expand both sides. The left side becomes \( x^2 + 2x + 1 \) and the right side becomes \( x^2 + 4x - 5 \). Set them equal: \( x^2 + 2x + 1 = x^2 + 4x - 5 \), and simplify to find \( 2x + 6 = 0 \), leading to \( x = -3 \). Now, let’s look at \( 3-\frac{x-2}{5}=2 \). Start by isolating the fraction: \( \frac{x-2}{5} = 1 \). Multiply both sides by 5, giving \( x - 2 = 5 \). Solving for \( x \) results in \( x = 7 \).

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy